Perfluorinated polymer fibre Bragg grating sensors for distributed low dose clinical X-ray measurements - Olusoji, Olugbenga Jeremiah; Kam, Wern; Ioannou, Andreas; Pospori, Andreas; McGuinness, Fintan; Woulfe, Peter; Kalli, Kyriacos; O’Keeffe, Sinead (My University, 2022)
Optical fibres have played an important role in the advancement of real-time dosimetry in clinical applications in recent years. Significant work has been done to increase precision and accuracy in detecting radiation doses during treatment, to avoid the negative effect that can ensue from irradiating healthy tissue around the tumour. The drive to develop distributed measurement in optical fibres has been limited to the slow scanning speed systems from optical time domain reflectometry (OTDR), however for radiotherapy dosimetry, with often short radiation pulse durations, fibre Bragg grating (FBG) interrogation is a better alternative because of the fast-scanning speed. The work presented here includes the preliminary results in the characterisation of CYTOP FBGs on exposure to X-ray radiation emitted from a clinical linear accelerator (linac) machine. A blue shifted linear response of the Bragg wavelength with sensitivity of 6.655 pm/Gy, 6.519 pm/Gy and 7.153 pm/Gy at the three main peaks (1522 nm, 1542 and 1561 nm), was recorded for a 9 Gy of radiation at a dose rate of 1.758 Gy/min with an amplitude fluctuation within the duration of radiation. The response demonstrates the potential for its use in low dose radiation dosimetry, providing for quasi-distributed sensing in radiotherapy.
Keywords: fibre Bragg grating sensors; low-dose clinical X-ray measurements